The performance of GPS baseline solution during northeast monsoon season in Malaysia - Yahya, Mohd. Hafiz; Kamaruddin, Md. Nor (2008)
Bringing heavy rainfall particularly to the east coast states of Peninsular Malaysia and western Sarawak, Northeast Monsoon occurs from November to March each year. Variability of tropospheric refractive indices caused by the inhomogeneity of dry gases and water vapour throughout this seasonal weather period induces latency in the satellite-to-receiver radiowave signal transmission. To date, Global Positioning System (GPS) has been responsible much of the local fast growing infrastructures, covering from the low cost and recreational uses to highly accurate and professional applications. As proper functioning of this space-based radio navigation satellites system receiver requires uninterrupted signal reception from at least four simultaneously available satellites, this paper examines the performance of GPS baseline solutions associated with relative positioning during the Northeast Monsoon period. Result shows that discrepancies on the computed three dimensional vectors can be expected during the Northeast Monsoon season. Better result in the GPS positioning can be expected based from the relatively short baseline compared to the long baseline. By examining the effect of the Saastamoinen model and the Hopfield model in data processing, these global tropospheric models tend to improve the ratio, reference variance and root mean square (RMS) in GPS baseline solutions. Nevertheless, no statistical differences can be seen based on the comparative analysis between these models on the result.